FUNGSI KOGNITIF DAN STATUS GIZI PADA LANSIA DI PUSKESMAS SEDAYU II BANTUL - Brune Indah Yulitasari; Latifatul Yumna; Julia Meranti (Jurnal Keperawatan Abdurrab, 2022)
Impaired cognitive function is one of the health problems experienced by the elderly. It can cause the elderly to experience setbacks or not be able to carry out daily activities independently. One of the factors that can cause the elderly to experience a decline in cognitive function is the condition of nutritional status in the elderly. This study aimed to identify the relationship between cognitive function and nutritional status in the elderly at Puskesmas Sedayu 2, Bantul, Yogyakarta. This type of research is quantitative correlation research with a cross-sectional approach design. The population in this study was the elderly aged 60 years and over. The sampling technique used was consecutive sampling with a total of 100 samples. The research instrument used the MMSE (Mini-Mental State Exam) and nutritional status by measuring weight, height, and calculating BMI. The analysis using the Pearson Product moment correlation test revealed there was no significant relationship between cognitive function and nutritional status. It is necessary to do further research related to cognitive function in the elderly.